2015
DOI: 10.1002/pssa.201532652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of X‐ray irradiation on the blinking of single silicon nanocrystals

Abstract: Photoluminescence (PL) intermittency (blinking) observed for single silicon nanocrystals (Si‐NCs) embedded in oxide is usually attributed to trapping/de‐trapping of carriers in the vicinity of the NC. Following this model, we propose that blinking could be modified by introducing new trap sites, for example, via X‐rays. In this work, we present a study of the effect of X‐ray irradiation (up to 65 kGy in SiO2) on the blinking of single Si‐NCs embedded in oxide nanowalls. We show that the luminescence characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For example, ligand passivated Si nanocrystals in a liquid were reported to exhibit no blinking [104], suggesting the key role of defects in the oxide and at the SiNC/SiO 2 interface at charge capture. However, x-rays irradiation of thick oxide samples did not result in strong changes in Si NC blinking, possibly due to self-annealing of oxide traps at room temperature [101].…”
Section: On/off Intermittency-blinkingmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, ligand passivated Si nanocrystals in a liquid were reported to exhibit no blinking [104], suggesting the key role of defects in the oxide and at the SiNC/SiO 2 interface at charge capture. However, x-rays irradiation of thick oxide samples did not result in strong changes in Si NC blinking, possibly due to self-annealing of oxide traps at room temperature [101].…”
Section: On/off Intermittency-blinkingmentioning
confidence: 88%
“…In general, one can distinguish two types of interval time distributions for this binary process. First, the exponential distribution, also known as 'random telegraph noise' [97][98][99][100][101], detected for thermally oxidized Si NCs. Second, the power-law distribution, typically observed for direct bandgap nanocrystals and porous silicon particles [74,102].…”
Section: On/off Intermittency-blinkingmentioning
confidence: 99%
“…Recently, we reported the effect of X-ray exposure on the PL of single Si/SiO 2 -QDs and we demonstrated that lifetime, emission energy, and linewidth were surprisingly unaffected up to the high dose of $65 kGy (SiO 2 ). 34 Although the preliminary study showed dot-to-dot variations of the blinking ON-and OFF-time constants as a function of X-ray dose, it was limited in terms of the number of samples/dots probed, blinking statistics, and maximum absorbed dose. In this letter, we analyze under identical conditions the irradiation effect for two types of core/shell QDs: CdSe/CdZnS and Si/SiO 2 .…”
mentioning
confidence: 99%
“…1 show that the PL of Si-QDs is intense even at $270 kGy, thus confirming and extending our previous study, which was limited to 65 kGy. 34 However, if we focus our attention on single luminescent Si-QDs, we can visually notice that different dots vary in luminescence intensity as a result of irradiation. Consequently, the X-ray irradiation is clearly influencing their photophysical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation